2013
DOI: 10.1590/s2176-94512013000300022
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of elastomeric chains related to the amount and time of stretching

Abstract: It was concluded that permanent deformation is directly proportional to the degree of stretching of the ECs assessed. The mean percentages found were 8.4% to 10% of stretching, and exceeding 20% (21.3%) when stretched by 40%, and reaching 56.6% permanent deformation when stretched 100% of their original length. Finally, the highest percentage of permanent deformation occurred during the first week and was not statistically significant after this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
3
12
0
2
Order By: Relevance
“…As shown in Figure 3C , the permanent deformation immediately after prestretch was positively correlated with the degree of prestretch, whereas no such correlation was observed when time condition was included ( Figure 3B ). Permanent deformation was positively correlated only with the constant strain set at the beginning of the experiment ( Figure 3D ), in agreement with the results of Yagura et al, 10 who found that permanent deformation was proportional to the stretching extent. Therefore, orthodontic synthetic elastomeric chains with properties altered by prestretch did not increase permanent deformation at weeks 4 and 8 during proper orthodontic treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 3C , the permanent deformation immediately after prestretch was positively correlated with the degree of prestretch, whereas no such correlation was observed when time condition was included ( Figure 3B ). Permanent deformation was positively correlated only with the constant strain set at the beginning of the experiment ( Figure 3D ), in agreement with the results of Yagura et al, 10 who found that permanent deformation was proportional to the stretching extent. Therefore, orthodontic synthetic elastomeric chains with properties altered by prestretch did not increase permanent deformation at weeks 4 and 8 during proper orthodontic treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Herein, we measured length changes every week, revealing that the degree of permanent deformation was less than that observed by Song and Kim, 17 which was thought to reflect the differences in the utilized materials. The curved form of the graph reflecting the temporal evolution of normalized permanent strain ( g X ( t )) was consistent with the results obtained by Yagura et al 10 Herein, permanent deformation was found to be proportional to the stretching extent ( Figure 3D ). In addition, the highest percentage of permanent deformation was observed during the first week, which agreed with the decrease of the large early-stage permanent deformation with time.…”
Section: Discussionsupporting
confidence: 90%
“…[4,9] The results of research conducted are consistent with research conducted by Mirhashemi et al where the decrease in strength after the first 24 h occurred at 20.7%-31.2% in elastomeric chains of thermoplastic materials and 9.3%-12.4% in elastomeric chains of thermoset materials. [5,8] The greatest decrease in strength that occurs after the first 24 h is also in accordance with the research conducted by Yagura et al, [10] where the greater the initial strength given to elastomeric chains, the greater the decrease in strength that occurs. Buchmann et al [3] and Mirhashemi et al [8] suggested that the decrease in strength up to the seventh day was caused by absorption of saliva and formation, which coincided with hydrogen adhesion between water molecules and elastomeric macromolecules.…”
Section: Discussionsupporting
confidence: 89%
“…Elastomers are considered important adjuvant materials in orthodontic treatment and have many clinical applications 1,2 . This refers especially to esthetic elastomers used in adult patients who are highly demanding about the esthetic appearance of orthodontic appliances 3,4 .…”
Section: Introductionmentioning
confidence: 99%